Nutrition and physiology of hybrid Eucalyptus urograndis in soil fertilized with sewage sludge - Zabotto, Alessandro Reinaldo; Gomes, Leticia Danielle Longuini; de Moura D'andréa Mateus, Caroline [UNESP]; Boas, Roberto Lyra Villas [UNESP]; Kanashiro, Shoey; Tavares, Armando Reis (Pensoft Publishers, 2020)
Sewage sludge is a residual pollutant product from the treatment of urban effluent and must be adequately processed before final disposal in order to avoid environmental contamination. The use of sewage sludge in agricultural and forestry areas can improve the physical, chemical and biological properties of soil; it can also be a source of nutrients, increasing crop productivity. Accordingly, this study aimed to evaluate the growth and development of hybrid Eucalyptus urograndis (Eucalyptus grandis x E. urophylla) seedlings cultivated in soil with different doses of sewage sludge. To accomplish this, hybrid E. urograndis seedlings were cultivated for 120 days in pots containing soil (dystrophic Red-Yellow Latosol-LVA) with different doses of sewage sludge (0, 30, 60 or 90 Mg ha-1). The experiment was carried out in a randomized complete block design consisting of four treatments, three replications with four plants per replication, totaling 48 plants. Biometric, biomass and physiological variables (chlorophyll, gaseous exchange, stomatal conductance and transpiration); in addition to macro-and micronutrient contents in leaves and soils of each treatment were evaluated. The treatments with sewage sludge were statistically superior to control treatment for all variables. Therefore, we recommend the application of 60 Mg ha-1 sewage sludge for the growth of hybrid Eucalyptus urograndis seedlings. Conversely, 90 Mg ha-1 sewage sludge inhibited hybrid E. urograndis root growth. Moreover, the use of sewage sludge as organic fertilizer in tropical soils is a viable and sustainable alternative for Eucalyptus cultivation.
Keywords: Biosolid; Eucalyptus; Fertilization; Organic nutrition